LEV VYGOTSKY’S SOCIOCULTURAL APPROACH AND AUTHENTIC MATERIALS IN EFL CLASSROOMS - Kirana, Dhinuk Puspita (Jurnal Bahasa Lingua Scientia, 2014)
There are barriers in teaching and learning foreign language but there are always ways in overcoming the problems. One of the most challenging tasks faced by (English as a Foreign Language)  EFL teachers is how to elicit the students’ interest so that they will be more motivated to learn and successfully develop their English proficiency. Educational psychology theories developed by Russian psychologist, Lev Vygotsky have been recognized as having great contribution to language education and teacher training. Education experts also insisted that in order to motivate the students, English which is presented in EFL classrooms should be authentic in order to immerse students into the real usage of English communication. This article discusses Vygotsky’s sociocultural approach and the authentic materials used in the classroom to develop students’ English proficiency.